Textbook Outcome as a Quality Metric in Liver Transplantation. Issue 5 (15th April 2022) - Schenk, Austin D.; Han, Jing L.; Logan, April J.; Sneddon, Jeffrey M.; Brock, Guy N.; Pawlik, Timothy M.; Washburn, William K.
Abstract : Background: Quality in liver transplantation (LT) is currently measured using 1-y patient and graft survival. Because patient and graft survival rates now exceed 90%, more informative metrics are needed. Textbook outcomes (TOs) describe ideal patient outcomes after surgery. This study critically evaluates TO as a quality metric in LT. Methods: United Network for Organ Sharing data for 25 887 adult LT recipients were used to define TO as patient and graft survival >1 y, length of stay ≤10 d, 0 readmissions within 6 mo, absence of rejection, and bilirubin <3 mg/dL between months 2 and 12 post-LT. Univariate analysis identified donor and recipient characteristics associated with TO. Covariates were analyzed using purposeful selection to construct a multivariable model, and impactful variables were incorporated as linear predictors into a nomogram. Five-year conditional survival was tested, and center TO rates were corrected for case complexity to allow for center-level comparisons. Results: The national average TO rate is 37.4% (95% confidence interval, 36.8%-38.0%). The hazard ratio for death at 5 y for patients who do not experience TO is 1.22 (95% confidence interval, 1.11-1.34; P ≤ 0.0001). Our nomogram predicts TO with a C-statistic of 0.68. Center-level comparisons identify 31% of centers as high performing and 21% of centers as below average. High rates of TO correlate only weakly with center volume. Conclusions: The composite quality metric of TO after LT incorporates holistic outcome measures and is an important measure of quality in addition to 1-y patient and graft survival.